Checklist of Herpetofauna in Sungai Mudal Park and Kembang Soka Waterfall - Qusway, Ana Ghoyatul; Sifa, Itsnaini Fadhilah (Proceeding International Conference on Science and Engineering, 2019)
Herpetofauna in Indonesia is very abundant, one of the richest areas of herpetofauna in Indonesia is in the Menoreh Mountain of Kulon Progo. Girimulyo started pioneering the natural tourist in the Kembang Soka Waterfall and Sungai Mudal Park. In 2012 the diversity in this place was researched by Qurniawan et al. This study aimed for renewing data of herpetofauna. The study was conducted from February to June 2018. This study used VES (Visual Encounter Survey) method, which works in combination with the belt transect method. A total of 22 Herpetofauna species has been found and identified in the Sungai Mudal Park and Kembang Soka Waterfall consists of 9 families, 5 families from the Amphibian class and 4 families from the Reptile class.